Here we have , f(x) = y= 7x-6
To find the inverse function of the given function, we need to follow some steps, which are:
First we need to switch x and y, that is
x= 7y-6
Next step is to solve for y, and for that, we need to add 6 to both sides
x+6=7y
Dividing both sides by 7, that is
![y = (x+6)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/q70zplod87ueb3b7m97clxh33uy6dtznj2.png)
Therefore,
![f^(-1)(x)= (x+6)/(7)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/exv46p7azp69prckuoi7baxnv258gqty6o.png)